Consistent long-term practice leads to consistent improvement: Benefits of self-managed therapy for language and cognitive deficits using a digital therapeutic - Liu, Hantian; Cordella, Claire; Ishwar, Prakash; Betke, Margrit; Kiran, Swathi (Frontiers in Digital Health, 2023)
Background Although speech-language therapy (SLT) is proven to be beneficial to recovery of post-stroke aphasia, delivering sufficiently high amounts of dosage remains a problem in real-world clinical practice. Self-managed SLT was introduced to solve the problem. Previous research showed in a 10-week period, increased dosage frequency could lead to better performance, however, it is uncertain if dosage still affects performance over a longer period of practice time and whether gains can be seen following practice over several months. Objective This study aims to evaluate data from a health app (Constant Therapy) to investigate the relationship between dosage amount and improvements following a 30-week treatment period. Two cohorts of users were analyzed. One was comprised of users with a consistent average weekly dosage amount and the other cohort was comprised of users whose practice had higher variability. Methods We conducted two analyses with two cohorts of post-stroke patients who used Constant Therapy. The first cohort contains 537 “consistent” users, while the second cohort contains 2,159 users. The 30-week practice period was split into three consecutive 10-week practice windows to calculate average dosage amount. In each 10-week practice period, patients were grouped by their average dosage into low (0-15 mins/week), medium (15-40 mins/week) and moderate dosage (greater than 40 mins/week) groups. Linear mixed-effects models were employed to evaluate if dosage amount was a significant factor affecting performance. Pairwise comparison was also applied to evaluate the slope difference between groups. Results For the consistent cohort, medium (β=.002, t17700=7.64, P<.001) and moderate (β=.003, t9297=7.94, P<.001) dosage groups showed significant improvement compared to the low dosage group. The moderate group also showed greater improvement compared to the medium group. For the variable cohort in analysis 2, the same trend was shown in the first two 10-week windows, however, in weeks 21-30, the difference was insignificant between low and medium groups (β=.001, t=1.76, P=.078). Conclusions This study showed a higher dosage amount is related to greater therapy outcomes in over 6 months of digital self-managed therapy. It also showed that regardless of the exact pattern of practice, self-managed SLT leads to significant and sustained performance gains.